Advanced crystal growth techniques with III-V boron compound semiconductors - Whiteley, Clinton E. (Kansas State University, 2011)
Semiconducting icosahedral boron arsenide, B[subscript]12As[subscript]2, is an excellent candidate for neutron detectors and radioisotope batteries, for which high quality single crystals are required. Thus, the present study was undertaken to grow B[subscript]12As[subscript]2 crystals by precipitation from metal solutions (nickel) saturated with elemental boron and arsenic in a sealed quartz ampoule. B[subscript]12As[subscript]2 crystals of 8-10 mm were produced when a homogeneous mixture of the three elements was held at 1150 °C for 48-72 hours and slowly cooled (3°C/hr). The crystals varied in color and transparency from black and opaque to clear and transparent. X-ray topography (XRT), Raman spectroscopy, and defect selective etching confirmed that the crystals had the expected rhombohedral structure and a low density of defects (5x10[superscript]7 cm[superscript]-2). The concentrations of residual impurities (nickel, carbon, etc) were found to be relatively high (10[superscript]19 cm[superscript]-3 for carbon) as measured by secondary ion mass spectrometry (SIMS) and elemental analysis by energy dispersive x-ray spectroscopy (EDS). The boron arsenide crystals were found to have favorable electrical properties (μ = 24.5 cm[superscript]2 / Vs), but no interaction between a prototype detector and an alpha particle bombardment was observed. Thus, the flux growth method is viable for growing large B[subscript]12As[subscript]2 crystals, but the impurity concentrations remain a problem.
Keywords: boron arsenide; crystal growth; neutron detectors; Chemical Engineering (0542)